1996
DOI: 10.1021/ma951184i
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitin/Polystyrene Hybrid Materials by Efficient Graft Copolymerization Based on Mercaptochitin

Abstract: Graft copolymerization of styrene onto mercaptochitin has been examined. Chitin was first tosylated to give tosylchitin, which was subsequently transformed into mercaptochitin. Athough the graft copolymerization was carried out in suspension, it proceeded efficiently to give chitin derivatives having polystyrene branches, a novel type of hybrid materials composed of a natural polysaccharide and a synthetic polymer. Under appropriate conditions, the grafting percentage reached 970%, indicating the high efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Kurita et al have reported the successful polymerisation of grafted chitin copolymers using 6-mercaptochitin from a-chitin as the trunk polymer Kurita, Hashimoto, Yoshino et al, 1996;Kurita et al, 2002). It was proposed that chitin copolymers could also be formed from related polymers prepared here, although these samples displayed lower DS values than those prepared by Kurita.…”
Section: Graft Polymerisationmentioning
confidence: 74%
See 3 more Smart Citations
“…Kurita et al have reported the successful polymerisation of grafted chitin copolymers using 6-mercaptochitin from a-chitin as the trunk polymer Kurita, Hashimoto, Yoshino et al, 1996;Kurita et al, 2002). It was proposed that chitin copolymers could also be formed from related polymers prepared here, although these samples displayed lower DS values than those prepared by Kurita.…”
Section: Graft Polymerisationmentioning
confidence: 74%
“…Thiolated chitosan polymers have been investigated for their metal binding capacity and selectivity (Cárdenas, Orlando, & Edelio, 2001;Lasko, Pesic, & Oliver, 1993), as macroinitiators for graft copolymerisation (Kurita, Hashimoto, Ishii, & Mori, 1996;Kurita, Hashimoto, Yoshino, Ishii, & Nishimura, 1996;Kurita, Inoue, & Harata, 2002) and for drug delivery and wound healing (Bernkop-Schnürch, Hornof, & Guggi, 2004;Guggi, Langoth, Hoffer, Wirth, & Bernkop-Schnürch, 2004;Hornof, Kast, & Bernkop-Schnürch, 2003;Hoyer, Schlocker, Krum, & Bernkop-Schnürch, 2008;Krauland, Guggi, & Bernkop-Schnürch, 2006;Masuko et al, 2005;Matsuda, Kobayashi, Itoh, Kataoka, & Tanaka, 2005;Werle & BernkopSchnürch, 2008). The thiol functional groups (R-SH) in the polymer can enhance the mucoadhesive properties of chitosan by forming disulfide bonds (RASASAR 0 ) with cysteine residues in proteins .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, the reactions have to be conducted under heterogeneous conditions in suspension owing to the insolubility of chitin and are thus generally poor in efficiency and reproducibility. Though insoluble, mercapto-chitin is a suitable radical initiator for styrene 7 and methyl methacrylate 8 to introduce side chains at the labile mercapto groups. As a new approach to graft copolymers, living poly(2-oxazoline)s were terminated t To whom all correspondence should be addressed.…”
mentioning
confidence: 99%